Impact of body mass index on outcomes in patients undergoing percutaneous coronary intervention for in-stent restenosis. (3rd October 2022) - Jones, D; Sartori, S; Cao, D; Nicolas, J; Spirito, A; Beerkens, F; Edens, M; Synder, C; Dangas, G; Mehran, R
Abstract: Background: Recent advances in drug eluting stents (DES) design have significantly decreased the rates of in-stent restenosis (ISR). Nonetheless, ISR remains a major problem, affecting 5–10% of patients undergoing percutaneous coronary intervention (PCI). Furthermore, PCI for ISR is often a poor prognostic factor for outcomes after the procedure. Historically, obese patients tended to have better outcomes when undergoing PCI, however it is unclear if this trend continues for the same population undergoing PCI for ISR. Purpose: Investigate the outcomes of patients undergoing PCI for ISR in the overweight and normal weight population. Methods: All patients undergoing PCI with DES implantation at a tertiary care center from January 2012 to December 2019 were included. Normal weight was defined as a body mass index (BMI) greater than or equal to 18.5 kg/m 2 and less than 25 kg/m 2, while overweight was defined as a BMI greater than or equal to 25 kg/m 2 . Patients with BMI <18.5 kg/m 2, underwent PCI for acute myocardial infarction (MI), or received a bare metal stent (BMS) were excluded. The primary outcome was major events (MACE), a composite of all-cause mortality, myocardial infarction (MI), and target vessel revascularization (TVR) up to one year after PCI. Secondary outcomes included individual components of the primary endpoint. Results: Out of 16, 234 patients with available data on BMI, 12, 444 (76.7%) were overweight and 3, 790 (23.3%) were normal weight. Among overweight patients, 2, 879 (23.1%) underwent PCI for ISR versus 815 (21.5%) of normal weight patients. Regardless of BMI status, patients undergoing PCI for ISR had higher rates of co-morbidities such as hypertension, hyperlipidemia, and diabetes mellitus than non-ISR counterparts. At one year post PCI, both overweight and normal weight patients undergoing PCI for ISR had increased risk of MACE (overweight: 18.4% vs. 6.7%; HR 2.83; 95% CI 2.50–3.20; normal weight: 18.8% vs. 7.8%, HR 2.43, 95% CI 1.95–3.04) when compared to non-ISR counterparts, mostly driven by TVR (overweight: 16% vs. 4.6%; HR 3.58; 95% CI 3.11–4.13; normal weight: 15.2% vs. 4.1%; HR 3.69; 95% CI 2.80–4.86). However, only overweight patients undergoing PCI for ISR had higher risk of all cause mortality (2.2% vs. 1.5%; HR 1.42; 95% CI 1.03–1.95) and MI (3.0% vs. 1.3%, HR 2.22; 95% CI 1.64–2.99) when compared to non-ISR counterparts (Figure 1). Conclusions: PCI for ISR was associated with increased risk of MACE, irrespective of body weight. The risks of all-cause mortality and MI in ISR vs non-ISR patients only reached statistical significance in overweight patients. Funding Acknowledgement: Type of funding sources: None.